Intrinsic and Extrinsic Elements in Pekal Songs: A Literary ‎Analysis of Man Pekal’s Salam Sakapoh Iban Album - Friandy Friandy; Kasmantoni Kasmantoni; Meddyan Heriadi (JPI: Jurnal Pustaka Indonesia, 2023)
This study analyzes the intrinsic and extrinsic elements of the Pekal songs in Salam Sakapoh Iban, an album by Man Pekal, to explore how these songs convey both literary aesthetics and socio-cultural meanings. Song lyrics, often considered poetic, serve as artistic expressions while simultaneously reflecting cultural values. Despite their significance, Pekal songs remain underexplored in Indonesian literary studies. This qualitative descriptive research examines ten selected songs through transcription, translation, classification, and thematic interpretation. Data were collected via textual analysis and interviews, distinguishing intrinsic elements (such as diction, imagery, concrete words, figurative language, rhyme; theme, emotion, tone, and message) and extrinsic elements (biographical, social, and value-based contexts). The findings reveal that Pekal songs merge aesthetic and cultural functions. Intrinsically, the songs utilize vivid diction, repetition, figurative imagery, and rhyme to express themes of love, longing, migration, solidarity, and cultural identity. Extrinsically, they reflect the composer’s biography, socio-cultural environment, and values such as care, obedience, religiosity, and historical memory. Songs like Maratau emphasize migration struggles, while Salam Sakapoh Iban foregrounds unity and tradition. The interplay between intrinsic and extrinsic elements demonstrates how Pekal songs function as both artistic and cultural texts, preserving identity and imparting moral teachings. These songs contribute to understanding local identity in a globalized world while maintaining ethnic values. This study concludes that analyzing Pekal songs enriches Indonesian literature and sustains regional identity amidst cultural transformation.